RESPON PERTUMBUHAN VEGETATIF TANAMAN JAGUNG MANIS (Zea mays L) TERHADAP BERBAGAI JENIS MULSA UNTUK PENGEMBANGAN BAHAN AJAR PADA KONSEP PERTUMBUHAN - Sri Wulandari '; Wan Syafii '; Mahendra ' ' (Biogenesis, 2014)
Research has been carried out in the Laboratory of Biology Teacher Training andEducation Faculty of University of Riau from April to August 2013. The goal of thisresearch is to determine the best type of mulch to trigger the vegetative growth ofsweet corn (Zea mays L. var. saccharata) and produce module on the concept ofdevelopment and growth concept for high school students. This research usedexperimental methods with randomized block design (CRD) with 5 treatments and 3replications so that there are 15 experimental units. Treatment are A 0 = without mulch,A 1 = mulch reeds, A 2 = mulch palm empty fruit bunches, A 3 = mulch black plastic, A 4 =white plastic bag. Biological parameters measured were plant height, stem diameter,fresh weight and dry weight. Physic-chemical parameters are soil temperature, soilmoisture, and soil pH. The data were analyzed by ANOVA and tested further byDMRT at 5% level. The results showed that the use of mulch influence on stemdiameter and dry weight of sweet corn plants, but not in the height and wet weight ofthe plant. The use of oil palm empty fruit bunches mulch gave best result on theparameter plant height (86,54 cm), stem diameter (1,80 cm), fresh weight (191,7 g)and sweet corn plant dry weight (43,33 g ). The results of this research can bedeveloped into module on the concept of plant growth for high school students withthe title of “Pengaruh Beberapa Jenis Mulsa Terhadap Pertumbuhan VegetatifTanaman Jagung”.Keywords: Corn, Dry weight, Mulch, Module, Plant height, Stem diameter, Vegetativegrowth, Wet weight